2002
DOI: 10.1002/hed.10162
|View full text |Cite
|
Sign up to set email alerts
|

First bite syndrome: A complication of surgery involving the parapharyngeal space

Abstract: Preservation of parotid gland tissue and a loss of its sympathetic nerve supply, whether by disruption of the cervical sympathetic chain as evidenced by a Horner's syndrome or more selective denervation by ligation of the external carotid artery with its accompanying sympathetic nerve plexus, were common features of all patients. This series supports the concept of parotid "sympathectomy" as an etiologic factor in FBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 7 publications
3
132
0
1
Order By: Relevance
“…2 First bite syndrome has previously been described only as a complication of parapharyngeal space surgery. [3][4][5][6] The main symptom is pain in the parotid and jaw, often with radiation to the ear, which lasts a few seconds and occurs with the first bite of each meal. 3 The symptoms are always worse with the first bite, and improve and resolve with subsequent bites, only to recur at the start of the next meal.…”
Section: Introductionmentioning
confidence: 99%
“…2 First bite syndrome has previously been described only as a complication of parapharyngeal space surgery. [3][4][5][6] The main symptom is pain in the parotid and jaw, often with radiation to the ear, which lasts a few seconds and occurs with the first bite of each meal. 3 The symptoms are always worse with the first bite, and improve and resolve with subsequent bites, only to recur at the start of the next meal.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also demonstrated that intrathecal fentanyl did not reduce the risk of postdural puncture headache with a 25G Quincke needle [2]. In addition to Al-metwalli's study there have been other reports of epidural morphine preventing headache after accidental dural puncture [3,4]. I have however, been unable to find any references to the effect of intrathecal diamorphine on the incidence of postdural puncture headache following spinal anaesthesia.…”
mentioning
confidence: 73%
“…Some evidences are in favor of this pathogenetic hypothesis. In fact, previous studies [2,3] described FBS to occur together with Horner's syndrome. Chiu [2] reported nine cases of FBS in a series of 12 patients undergoing resection of the cervical sympathetic trunk or presenting loss of sympathetic function documented by Horner's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Following this publication, several papers concerning FBS were published [2][3][4] and different clinical variants were reported. More than 95% of published cases correspond to postoperative syndromes following upper neck surgery, such as resection of mixed and/or cervical sympathetic nerve tumors, deep cervical lymph node dissection, parotid gland surgery, particularly involving its deep lobe, parapharyngeal and infratemporal fossa surgery, carotid bifurcation and/or internal carotid artery surgery, and resection of the styloid process.…”
Section: Introductionmentioning
confidence: 99%